Deubiquitinase USP13 alleviates doxorubicin-induced cardiotoxicity through promoting the autophagy-mediated degradation of STING - Liming Lin; Jibo Han; Diyun Xu; Zimin Fang; Bozhi Ye; Jinfu Qian; Xue Han; Julian Min; Xiaohong Long; Gaojun Wu; Guang Liang (Acta Pharmaceutica Sinica B)
Doxorubicin (Dox) is an anthracycline drug widely applied in various malignancies. However, the fatal cardiotoxicity induced by Dox limits its clinical application. Post-transcriptional protein modification via ubiquitination/deubiquitination in cardiomyocytes mediates the pathophysiological process in Dox-induced cardiotoxicity (DIC). In this study, we aimed to clarify the regulatory role and mechanism of a deubiquitinating enzyme, ubiquitin-specific peptidase 13 (USP13), in DIC. RNA-seq analysis and experimental examinations identified that cardiomyocyte-derived USP13 positively correlated with DIC. Mice with cardiac-specific deletion of USP13 were subjected to Dox modeling. Adeno-associated virus serotype 9 (AAV9) carrying cTNT promoter was constructed to overexpress USP13 in mouse heart tissues. Cardiomyocyte-specific knockout of USP13 exacerbated DIC, while its overexpression mitigated DIC in mice. Mechanistically, USP13 deubiquitinates the stimulator of interferon genes (STING) and promotes the autolysosome-related degradation of STING, subsequently alleviating cardiomyocyte inflammation and death. Our study suggests that USP13 serves a cardioprotective role in DIC and indicates USP13 as a potential therapeutic target for DIC treatment.